Biocultural diversity for food system transformation under global environmental change - Argumedo, Alejandro; Song, Yiching; Khoury, Colin K.; Hunter, Danny; Dempewolf, Hannes; Guarino, Luigi; Haan, Stef de (Frontiers Media, 2021)
Biocultural diversity is central to the nutrition, resilience, and adaptive capacity of Indigenous and traditional peoples, who collectively maintain the longest ongoing human experiences with the provision of food under environmental change. In the form of crops and livestock and associated knowledge on their cultivation and use, food-related biocultural diversity likewise underpins global food security. As food system transformation is increasingly recognized as an urgent priority, we argue that food security, sustainability, resilience, and adaptive capacity can be furthered through greater emphasis on conservation, use, and celebration of food-related biocultural diversity. We provide examples from the Parque de la Papa, Peru, a “food biocultural diversity neighborhood” which through advocacy and partnerships based around its diversity, has both enhanced local communities and contributed to food security at a much larger scale. We outline collaborative actions which we believe are important to up- and out-scale food biocultural diversity neighborhood successes. Further research and knowledge sharing are critical to better document, understand, track, and communicate the value, functions, and state of biocultural diversity in food systems. Expanded training and capacity development opportunities are important to enable the interchange of experiences and visions on food, health, sustainability and resilience, climate adaptation, equity and justice, and livelihood generation with others facing similar challenges. Finally, strengthened networking across food biocultural diversity neighborhoods is essential to their persistence and growth as they increasingly engage with local, national, and international organizations, based on shared interests and on their own terms, across five continents.